Bridging The Policy-Practice Gap In Vocational English For Hospitality: Aligning Isced And Iqf Competency Frameworks With Classroom Instruction - Susanti, Luh Eka; Apsari, Yanuarti; Palupiningsih, Angesti (Journal of Language and Applied Linguistics, 2026)
This study examines the discrepancy between international and national educational frameworks, specifically the International Standard Classification of Education (ISCED) and the Indonesian Qualification Framework (IQF/KKNI) and their implementation in English for Specific Purposes (ESP) instruction within vocational hospitality education, particularly in restaurant contexts. Although both frameworks emphasize competency-based learning and authentic workplace preparation, classroom practices frequently remain dominated by traditional approaches, including the use of general English textbooks, written examinations, and limited opportunities for authentic communicative practice or technological integration. The lack of specialized ESP training among instructors, combined with institutional resource constraints, further exacerbates this mismatch. As a consequence, many graduates possess theoretical linguistic knowledge but lack the communicative competence required in the hospitality service industry. Addressing this issue requires comprehensive curriculum reform, continuous teacher professional development, simulation-based pedagogical approaches, integration of digital technologies, and stronger collaboration with industry stakeholders. These measures are essential to bridge the gap between educational policy and practical workplace demands in vocational English education.